Tumor cell-derived LC3B+extracellular vesicles mediate the crosstalk between tumor microenvironment and immunotherapy efficacy in hepatocellular carcinoma via the HSP90α-IL-6/IL-8 signaling axis - Chen, Yong-Qiang (Clinical immunology (Orlando, Fla.), 2024)
Copyright © 2024 Elsevier Inc. All rights reserved.